Search for heavy Majorana neutrinos in mu(+/-)mu(+/-) + jets events inproton-proton collisions at root s=8TeV - (:unkn) unknown (ELSEVIER, 2015)
A search is performed for heavy Majorana neutrinos (N) using an event signature defined by two muons of the same charge and two jets (mu(+/-)mu(+/-)jj). The data correspond to an integrated luminosity of 19.7 fb(-1) of proton-proton collisions at a center-of-mass energy of 8TeV, collected with the CMS detector at the CERN LHC. No excess of events is observed beyond the expected standard model background and upper limits are set on vertical bar V-mu N vertical bar(2) as a function of Majorana neutrino mass mN for masses in the range of 40-500GeV, where V-mu N is the mixing element of the heavy neutrino with the standard model muon neutrino. The limits obtained are vertical bar V-mu N vertical bar(2) < 0.00470 for m(N) = 90GeV, vertical bar V-mu N vertical bar(2) < 0.0123 for m(N) = 200GeV, and vertical bar V-mu N vertical bar(2) < 0.583 for m(N) = 500 GeV. These results extend considerably the regions excluded by previous direct searches. (C) 2015 CERN for the benefit of the CMS Collaboration. Published by Elsevier B.V.
Keywords: CMS; Physics; Heavy neutrino; MASSES; NONCONSERVATION; LEPTONS